Fugitive Repair - Lewis, Jovan Scott (ACME, 2023)
As a Black Studies concept that traces the circumstances of (non)freedom of Black subjects, fugitivity is, in essence, an escaping or evasion of oppressive systems and structures. In Black Studies, fugitivity embodies the dual process of resistance and resilience of Black subjects who seek liberation from racism and systemic injustice and of reclaiming and exercising agency and autonomy in a world that constantly marginalizes and subjugates. In exploring the concept of fugitivity and its implications for the liberation of Black subjects, it becomes crucial to consider whether and if fugitivity serves as a position, a process, or a relation from which Black individuals and communities can bring about repair as complete liberation.